diff --git a/bip-DLEQ.mediawiki b/bip-DLEQ.mediawiki
index c03260be..71ed2637 100644
--- a/bip-DLEQ.mediawiki
+++ b/bip-DLEQ.mediawiki
@@ -48,7 +48,7 @@ Verifying the proof involves recreating ''R1'' and ''R2''
* Let ''R1 = s⋅G - e⋅A''.
* Let ''R2 = s⋅B - e⋅C''.
-This can be verified by substituing ''s = (k + e⋅a)'':
+This can be verified by substituting ''s = (k + e⋅a)'':
* ''s⋅G - e⋅A = (k + e⋅a)⋅G - e⋅A = k⋅G + e⋅(a⋅G) - e⋅A = k⋅G + e⋅A - e⋅A = k⋅G''.
* ''s⋅B - e⋅C = (k + e⋅a)⋅B - e⋅C = k⋅B + e⋅(a⋅B) - e⋅C = k⋅B + e⋅C - e⋅C = k⋅B''.